WHAT NEW NORM? THE ROLE OF SOCIAL MEDIA IN COVID-19 - Viloshinni Murali; Normahfuzah Ahmad (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This research is developed to study COVID-19 and the use of social media among students. Specifically, on social media applications used by tertiary university students in Malaysia to obtain current information regarding the COVID-19 outbreak. Apart from that, the pilot study was conducted prior to distributing the main questionnaire to ensure that questions designed are suitable. Changes were made upon feedback received from pilot study. Finding suggests students are aware on the implementation of Standard Operating Procedures by the Malaysian government. However, students cannot fully differentiate the differences to the variations of imposed lockdowns. The finding also shows that Malaysian university students are aware of Malaysia’s current issues and the many variations of rules and regulations which have become the new norm. This study expands further literature on the use of social media particularly among the young generation. Additionally, this study adds new knowledge to studies pertaining to the use of social media in times of health crisis in the nation.